Records of semiotic representation: experience in teaching quadratic functions with students of Integrated Middle School - Santana, Linus; Gualandi, Jorge; Soares, Maria (Educação Matemática Debate, 2019)
In the context of the need to provide students with conditions to represent a mathematical object in various ways, research was developed as a way of investigating how students move between the forms of quadratic function registers. This was developed in a qualitative way, with the use of an exploratory study with the students of the 1st grade of the Integrated High School through lists of tasks, besides being realized in stages, among them, the discussion of the tasks in order to comprise the various records presented by the students. All research had support in Raymond Duval’s Theory of Semiotic Representation Records, with emphasis on conversion. The results verified can contribute to rethink the pedagogical practice of how mathematical contents can be worked with students in their various approaches and forms, allowing reflections in the teaching-learning process. Keywords: Semiotic Representation. Quadratic Functions. Teaching Learning.